Circulating androgens are associated with mood disturbances in young postmenopausal women. (April 2015) - Lambrinoudaki, I.; Bouziou, G.; Armeni, E.; Spyropoulou, A.; Koundi, K.; Rizos, D.; Augoulea, A.; Alexandrou, A.; Creatsa, M.; Panoulis, C.; Dendrinos, S.; Leonadrou, A. A.; et al.
Abstract: Objectives We aimed to evaluate the association between circulating androgens and the presence of psychological symptoms in a sample of healthy middle-aged women. Methods Psychological and depressive symptoms were evaluated in a total of 207 postmenopausal women, using the Symptom Checklist-90-R (SCL-90R) and the Zung Depression Scale, respectively. We investigated the associations between the SCL-90R and Zung Scale scores, and anthropometric, lifestyle parameters, as well as serum levels of androgens. Results The free androgen index was positively associated with scores of depression (b-coefficient ± standard error (SE) = 0.2 ± 0.2, p = 0.040), anxiety (b-coefficient ± SE = 0.2 ± 0.2, p = 0.028), anger/aggressiveness (b-coefficient ± SE = 0.3 ± 0.2, p = 0.026), psychotism (b-coefficient ± SE = 0.3 ± 0.1, p = 0.013) as well as with the global index of the SCL-90R scale (b-coefficient ± SE = 0.2 ± 0.1, p = 0.036), while sex hormone binding globulin was negatively associated with depression (b-coefficient ± SE = −0.2 ± 0.0, p = 0.046) and psychotism (b-coefficient ± SE = −0.2 ± 0.0, p = 0.047). These associations were independent of vasomotor symptomatology, smoking and hormone therapy intake and were more pronounced in younger (≤ 5.5 years) compared to older postmenopausal women. Levels of dehydroepiandrosterone sulfate were positively associated with interpersonal sensitivity (b-coefficient ± SE = 0.3 ± 0.3, p = 0.042), psychotism (b-coefficient ± SE = 0.4 ± 0.2, p = 0.007) and the global index (b-coefficient ± SE = 0.3 ± 0.2, p = 0.040) in women < 5.5 years postmenopausal. No significant associations were observed between the Zung or Greene Scale scores and levels of androgens. Conclusion Higher androgenicity was positively associated with symptoms of anxiety and depression in postmenopausal women. These associations were stronger in women closer to the menopausal transition, a finding which may suggest that menopause rather than aging may mediate the association of androgens with mood disorders.